The Three In-frame ATG, Clustered in the Translation Initiation Sequence of Human Factor IX Gene, Are Required for an Optimal Protein Production - Enjolras, Nathalie; Rodriguez, Marie-Hélène; Plantier, Jean-Luc; Maurice, Marielle; Attali, Olivier; Négrier, Claude (Thrombosis and Haemostasis, 1999)
Three in-frame potential methionine codons have been identified in human factor IX gene and are clustered at amino acids -46, -41 and -39. In view of initiating a gene therapy approach, human factor IX production has been evaluated after modifications of these first three in-frame translation start sites. To characterize the most efficient translation initiation context, five factor IX cDNA expression vectors directed by CMV promoter-enhancer were generated. These vectors contained different starting site combinations including one, two or three ATG. A quantitative analysis of factor IX production in stably transfected CHO cells and in a rabbit reticulocyte lysate cell free system revealed the ability of all single site to generate fully active factor IX. However, the factor IX production level increased with the ATG number and the wild type (WT) cDNA bearing the 3 ATG induced the highest protein production. A truncated intron I of factor IX, previously suggested of having an expression-augmenting activity, was also placed in the WT factor IX cDNA. In stably transfected CHO cells, a 8-fold increase in protein production was measured. These results show that at least in vitro, the presence of the three ATG seems to be crucial for a maximal factor IX production. The data also suggest that both the three ATG and the truncated intron I are required for an optimal factor IX production in a perspective of a human gene therapy of haemophilia.
Keywords: Factor IX; translational initiation; CHO cells; factor IX production; factor IX intron I